Age of Mother, Age of Pregnancy, and Neonatorum Asphyxia in Kaur Hospital - Wayterlis Apriani; Awal Isgiyanto; Yuliana Yuliana (Jurnal Sains Kesehatan, 2018)
Asphyxia can lead to complications in babies born including death in newborns. This study aimed to determine the relationship between maternal age and gestational age with the incidence of Neonatal Asphyxia in Kaur Hospital. This type of research was Analytical Survey with Case Control design. The population in this study were all mothers and babies born in 2016 as many as 270 people and who experienced asphyxia as many as 68 people. Data collection in this study used secondary data. Data analysis used Chi-Square, Contingency Coefficient and OR analysis. The results showed that there were 68 people (50%) asphyxia with 79 people (58.1%) aged 20-35 years, (3) 84 people (61.8%) mature, there was a significant relationship between the age of mothers with asphyxia in Kaur Hospital was in a close relationship category, and there was a significant relationship between the gestational age of asphyxial mothers in  Kaur  Hospital with the moderate relationship category. It was expected that health workers, especially midwives, can approach every pregnant woman and provide counseling about the importance of regulating maternal age and gestational age before                  the process of pregnancy and childbirth so as to reduce the risk of asphyxia. Keywords: asphyxia, maternal age, gestational age